The effect of PKA-mediated phosphorylation of ryanodine receptor on SR Ca2 + leak in ventricular myocytes. (March 2017) - Bovo, Elisa; Huke, Sabine; Blatter, Lothar A.; Zima, Aleksey V.
Abstract: Functional impact of cardiac ryanodine receptor (type 2 RyR or RyR2) phosphorylation by protein kinase A (PKA) remains highly controversial. In this study, we characterized a functional link between PKA-mediated RyR2 phosphorylation level and sarcoplasmic reticulum (SR) Ca 2 + release and leak in permeabilized rabbit ventricular myocytes. Changes in cytosolic [Ca 2 + ] and intra-SR [Ca 2 + ]SR were measured with Fluo-4 and Fluo-5N, respectively. Changes in RyR2 phosphorylation at two PKA sites, serine-2031 and -2809, were measured with phospho-specific antibodies. cAMP (10 μM) increased Ca 2 + spark frequency approximately two-fold. This effect was associated with an increase in SR Ca 2 + load from 0.84 to 1.24 mM. PKA inhibitory peptide (PKI; 10 μM) abolished the cAMP-dependent increase of SR Ca 2 + load and spark frequency. When SERCA was completely blocked by thapsigargin, cAMP did not affect RyR2-mediated Ca 2 + leak. The lack of a cAMP effect on RyR2 function can be explained by almost maximal phosphorylation of RyR2 at serine-2809 after sarcolemma permeabilization. This high RyR2 phosphorylation level is likely the consequence of a balance shift between protein kinase and phosphatase activity after permeabilization. When RyR2 phosphorylation at serine-2809 was reduced to its "basal" level (i.e. RyR2 phosphorylation level in intact myocytes) using kinase inhibitor staurosporine, SR Ca 2 + leak was significantly reduced. Surprisingly, further dephosphorylation of RyR2 with protein phosphatase 1 (PP1) markedly increased SR Ca 2 + leak. At the same time, phosphorylation of RyR2 at serine 2031 did not significantly change under identical experimental conditions. These results suggest that RyR2 phosphorylation by PKA has a complex effect on SR Ca 2 + leak in ventricular myocytes. At an intermediate level of RyR2 phosphorylation SR Ca 2 + leak is minimal. However, complete dephosphorylation and maximal phosphorylation of RyR2 increases SR Ca 2 + leak. Highlights: Phosphorylation of RyR2 by protein kinase A (PKA) regulates sarcoplasmic reticulum (SR) Ca 2 + leak in ventricular myocytes. Complete dephosphorylation and maximal phosphorylation of RyR2 increase SR Ca 2 + leak. An intermediate level of RyR2 phosphorylation reduces SR Ca 2 + leak to its minimal level. Among several phosphorylation sites on RyR2, phosphorylation of serine 2809 has the most profound effect on RyR2 function.